Prevalence and risk factors of barotrauma in Covid-19 patients admitted to an intensive care unit in Kuwait; a retrospective cohort study. (March 2021) - Elsaaran, Hussein; AlQinai, Shamlan; AlTarrah, Dana; Abdulrasoul, Mahdi; Al-Youha, Sarah; Almazeedi, Sulaiman; Al-Haddad, Mohannad; Jamal, Mohammad H.; Al-Sabah, Salman
Abstract: Background: The development of barotrauma has been suggested to complicate the management of mechanically ventilated COVID-19 patients admitted to the intensive care unit (ICU). This study aims to identify potential risk factors associated with the development of barotrauma related complications in COVID-19 patients receiving mechanical ventilation. Methods: A retrospective cohort study was carried out in a single COVID-19 designated center in Kuwait. Three hundred and forty-three confirmed COVID-19 patients transferred and/or admitted to our institution between February 26, 2020 and June 20, 2020 were included in the study. All patients were admitted into the ICU with the majority being mechanically ventilated (81.3%). Results: Fifty-four (15.4%) patients developed barotrauma, of which 49 (90.7%) presented with pneumothorax, and 14.8% and 3.7% due to pneumomediastinum and pneumopericardium respectively. Of those that developed barotrauma, 52 (96.3%) patients were in acute respiratory distress syndrome (ARDS). Biochemically, the white blood cells (p = 0.001), neutrophil percentage (p = 0.012), lymphocyte percentage (p = 0.014), neutrophil: lymphocyte ratio (NLR) (p=<0.001) and lactate dehydrogenase (LDH) (p = 0.002) were found to be significantly different in patients that developed barotrauma. Intubation due to low level of consciousness (p = 0.007), a high admission COVID-GRAM score (p = 0.042), and a positive-end expiratory pressure (PEEP) higher than the control group (p = 0.016) were identified as potential risk factors for the development of barotrauma. Conclusion: Patients infected with COVID-19 have a significant risk of developing barotrauma when receiving invasive mechanical ventilation. This poses a substantial impact on the hospital course of the patients and clinical outcome, correlating to a higher mortality rate in this cohort of patients. Highlights: The development of barotrauma in mechanically COVID-19 patients complicates their management and hospital course. There is a high incidence rate (15.4%) of developing barotrauma related complications in COVID-19 ICU patients. ARDS is a major risk factor for the development of barotrauma in mechanically ventilated COVID-19 patients. Various biochemical markers as well as a high COVID-GRAM score is associated with the development of barotrauma. The development of barotrauma in COVID-19 patients is associated with a dismal clinical outcome.